Ethically minded consumer behavior of Generation Z in Vietnam: The impact of socialization agents and environmental concern - Tri D. Le; Hoang Duc Tran; Thi Que Huong Hoang (Cogent Business & Management, 2022)
With a young population structure, young consumers in Vietnam have been becoming a driving force and a major purchasing power behind the economic development. While ethical issues associated with consumerism have been a topic of discussion in the society, young consumers have stepped up to the plate by showing a positive support for being ethical consumers. It is still unclear, however, whether they are willing to actualize their perspective, as the alleged attitude-behavior gap is still commonplace. This research attempted to examine the influence of socialization agents and environmental concern on the ethically minded consumer behavior (EMCB) of young consumers by drawing on the socialization framework. The context of this research is Generation Z in Vietnam, the generation who has been growing up with technology but has been received lack investigation. With a sampling of 230 young consumers based in Ho Chi Minh City, results demonstrate that intimate relationships have a significant impact on young consumers' behavior towards dimensions of EMCB. In particular, family and peers exert substantial effect on young consumers' tendency to pay more for an ethical product as well as to purchase eco-friendly goods. Media, on the contrary, is not a significant determinant.
Keywords: 650; environmental concern; ethical consumption; ethically minded consumer behavior; Generation Z; socialization agents